A case study comparison of engaging community activists to prevent gender-based violence in Peru and Rwanda. Issue 10 (3rd October 2022) - Stern, Erin; Batista, Murylo; Shannon, Geordan; Heise, Lori; Mannell, Jenevieve
ABSTRACT: Community mobilisation is recognised as an important strategy to shift inequitable gender norms and ensure an enabling environment to prevent gender-based violence (GBV). Yet there is a need to better understand the factors that facilitate effective community activism in particular contexts. Although fundamental to the success of mobilisation programmes, there is also limited appreciation of the experiences and agency of engaged community activists. This paper draws on qualitative evaluations from two community mobilisation GBV prevention programmes: the Gender Violence in the Amazon of Peru (GAP) Project and the Indashyikirwa programme in Rwanda. In Peru, participatory data was collected, in addition to baseline and endline interviews with 8 activists. In Rwanda, baseline and endline interviews and observations were conducted with 12 activists, and interviews were conducted with 8 staff members. The data was thematically analysed, and a comparative case study approach was applied to both data sets. The comparative study identified similar programmatic aspects that could hinder or enable activist's engagement and development, and how these are embedded within contextual social and structural factors. We discuss these insights in reference to the current emphasis in public health on individualistic programming, with insufficient attention to how wider environments influence violence prevention programming.